Isolation of Mesophyll Protoplasts from Mediterranean Woody Plants for the Study of DNA Integrity under Abiotic Stress - Kuzminsky, Elena; Meschini, Roberta; Terzoli, Serena; Pavani, Liliana; Silvestri, Cristian; Choury, Zineb; Scarascia-Mugnozza, Giuseppe (Frontiers in Plant Science, 2016)
Abiotic stresses have considerable negative impact on Mediterranean plant ecosystems and better comprehension of the genetic control of response and adaptation of trees to global changes is urgently needed. The Single Cell Gel Electrophoresis assay could be considered a good estimator of DNA damage in an individual eukaryotic cell. This method has been mainly employed in animal tissues, because the plant cell wall represents an obstacle for the extraction of nuclei; moreover, in Mediterranean woody species, especially in the sclerophyll plants, this procedure can be quite difficult because of the presence of sclerenchyma and hardened cells. On the other hand, these plants represent an interesting material to be studied because of the ability of these plants to tolerate abiotic stress. For instance, holm oak (Quercus ilex L.) has been selected as the model plant to identify critical levels of O3 for Southern European forests. Consequently, a quantitative method for the evaluation of cell injury of leaf tissues of this species is required. Optimal conditions for high-yield nuclei isolation were obtained by using protoplast technology and a detailed description of the method is provided and discussed. White poplar (Populus alba L.) was used as an internal control for protoplast isolation. Such a method has not been previously reported in newly fully developed leaves of holm oak. This method combined with Single Cell Gel Electrophoresis assay represents a new tool for testing the DNA integrity of leaf tissues in higher plants under stress conditions.